Strategi Pembelajaran Kurikulum Outcome Base Education Dengan Menggunakan Actificial Intelligence Bard - APUD SAEPUDIN, ELI; Dede Qodrat Al Wajir; Parko Prahima; Arief Rachman (Journal Education Innovation (JEI), 2024)
Students always complain when college assignments pile up to find the right solution at this time there is an Outcome Based Education (OBE) curriculum learning strategy by utilizing Artificial Intelligence (AI) Bard as a learning media is expected to facilitate students in completing college assignments. AI Bard as an educational chatbot offers easy access to information and real-time assignment guidance. Its application in OBE learning is expected to improve material understanding, learning independence, and student learning outcomes. The research method in this study uses a descriptive approach with qualitative. The purpose of this research is to facilitate students in making college assignments quickly, precisely, efficiently.